Anita O'Donnell Liden Heads Maritime Academy Committee - Vallejo Times-Herald (Vallejo Times-Herald)
The distinction of being the only woman to head a Vallejo Chamber of Commerce committee during the current year is given to Anita O'Donnel Liden, chairman of the California Maritime Academy Committee. The recent appointment by Edward H. Case, Chamber of Commerce president, makes one more aware of Vallejo's All-America city qualities.